Painful Subjects: Treating Chronic Pain among People Living with HIV in the Age of Opioid Risk. (5th November 2020) - Carroll, Jennifer J.; Lira, Marlene C.; Lunze, Karsten; Colasanti, Jonathan A.; del Rio, Carlos; Samet, Jeffrey H.
Abstract: Public narratives often attribute the opioid overdose epidemic in the United States to liberal prescribing practices by health care providers. Consequently, new monitoring guidelines for the management of opioid prescriptions in patients with chronic pain have become recognized as key strategies for slowing this tide of overdose deaths. This article examines the social and ontological terrain of opioid‐based pain management in an HIV clinic in the context of today's opioid overdose epidemic. We engage with anthropological analyses of contemporary drug policy and the nonverbal/performative ways patients and clinicians communicate to theorize the social context of the opioid overdose epidemic as a "situation, " arguing that the establishment of new monitoring strategies (essentially biomedical audit strategies) trouble patient subjectivity in the HIV clinic—a place where that subjectivity has historically been protected and prioritized in the establishment of care.